School & famlily in the youngster’s resilience configuration - De la Cruz Reyes, Miriam; Muñoz Velazquez, Selene (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Resilience as an element that positively influences school success, describes the personal, family, school and contextual elements that configured, and each of the elements are discussed with the cases individuals of young people who attend an inserted secondary school in a context considered to be of high social risk in México. It is about of a qualitative work with phenomenological perspective. The analysis of the data made it possible to identify that the students respond positively to some of the attributes that are needed for the development of resilience, while the family and school become spaces of tensión.